2021
DOI: 10.1021/acschemneuro.1c00477
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Anosmia Caused by Symptoms of COVID-19 and Emerging Treatments

Abstract: The occurrence of anosmia, the loss or change in sense of smell, is one of the most common symptoms of COVID-19 experienced by almost 53% of those affected. Several hypotheses explain the mechanism of anosmia in patients suffering from COVID-19. This study aims to review the related mechanisms and answer the questions regarding COVID-19-related anosmia as well as propose a new strategy for treatment of long-term anosmia as a result of COVID-19 infection. This paper covers all of the studies investigating olfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 87 publications
0
58
0
1
Order By: Relevance
“…(3) Maria Ines Mitrani et al found that amniotic fluid-derived extracellular vesicle biologic could be used to treat respiratory disorders [ 53 ]. (4) Najafloo R et al proposed a comprehensive approach for the treatment of anosmia [ 54 ]. (5) Luckos M et al used EEG neurofeedback to treat cognitive dysfunctions after long COVID-19 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…(3) Maria Ines Mitrani et al found that amniotic fluid-derived extracellular vesicle biologic could be used to treat respiratory disorders [ 53 ]. (4) Najafloo R et al proposed a comprehensive approach for the treatment of anosmia [ 54 ]. (5) Luckos M et al used EEG neurofeedback to treat cognitive dysfunctions after long COVID-19 [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these methods, autologous superficial cutaneous nerves are known as the gold standard for bridging the nerve gap (>30 mm); however, there are several drawbacks, including major surgical risks, autologous graft rejection, infection, donor shortage, and the likelihood of further surgeries [ 11 ]. Tissue engineering (TE) proposes a promising alternative approach to overcome the existing challenges in tissue regeneration [ 12 , 13 , 14 ]. To successfully achieve neural regeneration, various factors, including topographical, chemical, mechanical, and electrical cues, should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In the small minority of patients with persistent anosmia, delayed recovery may be secondary to severe olfactory epithelium inflammation causing scarring and impairment of regeneration, 65 or damage to the olfactory receptor neurons and stem cell neurons. 63 In post-viral anosmia due to non-COVID-19 infections, the small subset of patients who experience permanent olfactory loss was similarly found to have virus-induced sensory neuronal damage. 66 Currently, the clinical significance of olfactory cleft opacification in COVID-19-associated OD is not fully known.…”
Section: Discussionmentioning
confidence: 99%